Differences in the Development of Motor Skills in Portuguese Children Aged 12 Months after 3 Years of COVID-19 Confinement - Miguel Rebelo; Rui Paulo; Samuel Honório; João Petrica; Marco Batista; Pedro Duarte-Mendes; Catarina Marques; João Serrano (MDPI AG, 2024)
(1) Background: The objective of the study was to verify the effects of COVID-19 confinement on motor skills through a longitudinal study in Portuguese children who were one year old at the beginning of the pandemic. (2) Methods: The sample consisted of 88 children of both sexes, in the pre-COVID-19 assessment, they were 13.31 ± 2.4 months old and in the post-COVID-19 assessment, the same children were already 49.31 ± 2.5 months old. Motor skills were assessed using the PDMS-2 scales. For the statistical analysis, the Kolmogorov-Smirnov test was used to test normality, and the Wilcoxon test was used to compare the results of the two assessments in the same sample. (3) Results: There were statistically significant differences in all motor skills assessed, with children presenting, on average, worse results in all global motor skills in the post-COVID-19 assessment, as opposed to fine motor skills, showing better results in the post-COVID-19 assessment. (4) Conclusions: These results show the negative impact of the pandemic on children evaluated with a special emphasis on global motor skills, with the majority demonstrating values considered below average for their age, noting that the pandemic protocols may have had serious consequences on children's motor development, warning professionals who deal daily with children in these age groups about the importance of stimulating global motor skills.